Investigating the antifungal effect of alcoholic extract of Butternut squash on Candida albicans isolated from vaginal infection - Azam Ghorbannia-Delaver; Issa Gholampour-Azizi; Atefeh Bozorgi; Faezeh Hassanzadeh (Chronic Diseases Journal)
BACKGROUND: Vaginal candidiasis is one of the most important fungal diseases in humans. Butternut squash (B. squash) has antifungal effects. This study investigated the effect of alcoholic extracts of B. squash on Candida albicans (C. albicans).